Aktivitas Promosi Melalui Media Sosial terhadap Proses Keputusan Pembelian Konsumen pada PD. Astiga Jaket Kulit Garut - Wati Susilawati (Fakultas Ekonomi Universitas Garut, 2017)
This study aims to identify the Influence of Promotion Through Social Media Against Consumer Purchase Decision Process in PD. Astiga Leather Garut Jacket The research method used in this research is descriptive research method and survey technique analysis. The sampling technique used in this research is using non propability sampling technique with the total population of 190 people, while the number of respondents is 66 respondents ie PD customers. Astiga Leather Garut Jacket. Based on the results of data processing obtained correlation which shows there is a strong relationship between Promotion Through Social Media Against Consumer Purchase Decision Process in PD. Astiga Leather Garut Jacket. While from the results of hypothesis testing obtained that the variable Promotion Through Social Media has a positive and significant impact on consumer purchasing decision Decision in PD. Astiga Leather Garut Jacket. Based on the calculation of coefficient of determination obtained. This. implies that the change in the variable value of the Purchase Decision process. Explained by the variable of Promotion Through social media influenced by other variables not examined.